The sandlot - Guiry, Thomas, 1981-; Vitar, Mike, 1978-; Renna, Patrick, 1979-; Allen, Karen, 1951-; Leary, Denis; Jones, James Earl.; Evans, David Mickey; Gunter, Robert; De la Torre, Dale.; Gilmore, William S.; Twentieth Century-Fox Film Corporation; Island World (Firm); et al. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2001)
Set in the early 1960's, this comedy focuses on a fifth grader who can't throw a baseball but is recruited by the leader of a neighborhood gang to play on the nearby sandlot field. It's the beginning of a summer he'll never forget.
Widescreen and pan and scan versions.
Originally released as a motion picture in 1993.
Special features include featurette, theatrical trailer and TV spots.
Director of photography, Anthony B. Richmond; editor, Michael A. Stevenson; music, David Newman.
Tom Guiry, Mike Vitar, Patrick Renna, Karen Allen, Denis Leary, James Earl Jones.
Rated PG.
Keywords: Baseball -- Juvenile drama; Comedy films; Feature films; Films for the hearing impaired